112 INTEGRATED CARE PROGRAMME FOR OLDER PEOPLE (ICPOP) IN A RURAL SETTING—ROLE OF ADVANCED NURSE PRACTITIONER (ANP). (18th November 2021) - Shiel, E; Costello, M; McCarthy, C; Murphy, R; McDermott, C; Geoghegan, J; Mannion, E; Conry, M; Flanagan, L; Moroney, E; Bhaoill, C U; Walsh, C; et al.
Abstract: Background: Sláintecare advocates for right care, in the right place at the right time. ANPs for Older Persons in the community are uniquely placed to deliver care as close as possible to the older person's home and to lead a holistic, flexible model of care minimising admission to acute care and maximising existing local resources. A pilot programme aimed at providing ANP led comprehensive geriatric assessment (CGA) (with Geriatrician support) to older people in a defined area commenced in June 2019. This pilot was part of a larger Hub and Spoke model funded by Sláintecare which gave additional MDT support. Methods: A referral template was designed. Criteria for referral included; age > 75 years, Rockwood Frailty Scale 4–6 (focusing on Falls, Cognitive Impairment and Complex Frailty). Older people on the cusp of requiring long term care (LTC) were also prioritised. A prospective database of patients was maintained by the ANP to evaluate the service. Results: From June 2019 to August 2021, 156 patients received an ANP led CGA, mostly conducted in the home. 247 reviews were conducted at the local spoke clinic and 46 joint ANP/Geriatrician home visits. Majority of referrals were from GP (n = 69), hospital (n = 30), LTC reviews (n = 22) and Community Nursing Units (CNUs) (n = 19). 449 outpatient appointments have been removed from the tertiary referral centre. Independent case load management from the ANP includes further appointments, telephone follow up/advice and she is a point of contact where crises arise before referral to acute services. 99% of patients surveyed reported satisfaction with the service especially the ease of local access and home visits. Conclusion: Older Persons' ANP can provide longitudinal care pathways for older adults in the community in conjunction with ICPOP and local CNUs, intervening before crises emerge and providing continuity of care and an alternative to acute care.